2022
DOI: 10.3390/cells11101691
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Reduces SARS-CoV-2 Replication In Vitro through Downregulation of D2 Receptors and Upregulation of Type-I Interferons

Abstract: Recent evidence suggests that SARS-CoV-2 hinders immune responses via dopamine (DA)-related mechanisms. Nonetheless, studies addressing the specific role of DA in the frame of SARS-CoV-2 infection are still missing. In the present study, we investigate the role of DA in SARS-CoV-2 replication along with potential links with innate immune pathways in CaLu-3 human epithelial lung cells. We document here for the first time that, besides DA synthetic pathways, SARS-CoV-2 alters the expression of D1 and D2 DA recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 67 publications
1
20
0
2
Order By: Relevance
“…175,176 Recently, it was indicated that dopamine can suppress the NLRP3 inflammasome by stimulating its ubiquitination and degradation, which has been related to either D1DR or D2DR pathways. 174 It is critical to explore the interaction between SARS-CoV-2 and dopaminergic receptors and its effects on the respiratory system and immune response. Such information is invaluable for the development of effective COVID -19 treatments.…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 Relationship...mentioning
confidence: 99%
See 3 more Smart Citations
“…175,176 Recently, it was indicated that dopamine can suppress the NLRP3 inflammasome by stimulating its ubiquitination and degradation, which has been related to either D1DR or D2DR pathways. 174 It is critical to explore the interaction between SARS-CoV-2 and dopaminergic receptors and its effects on the respiratory system and immune response. Such information is invaluable for the development of effective COVID -19 treatments.…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 Relationship...mentioning
confidence: 99%
“…It can down-regulate D2 family receptors and may be considered for hindering SARS-CoV-2 infection and restraining hyper-inflammation to prevent tissue damage. 174 Within this view, dopamine or D2 receptor agonists were able to inhibit key pro-inflammatory cytokines, including IL-6 and TNF-alpha, as well as NLRP3/IL-1b and TRL4/ HMGB1 pathways, as an index of COVID-19 severity. 175,176 Recently, it was indicated that dopamine can suppress the NLRP3 inflammasome by stimulating its ubiquitination and degradation, which has been related to either D1-Receptor or D2-Receptor pathways (Figure 7).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 and Potentia...mentioning
confidence: 99%
See 2 more Smart Citations
“…Positive chronotropic (e.g. dopamine) agents are considered for atrioventricular block, instead of the transvenous pacemaker to minimize personal protective equipment use and healthcare worker's risk (Limanaqi et al, 2022). It was suggested to postpone permanent pacemaker implantation to allow for an improvement of bradycardia (Kochav et al, 2020).…”
Section: Treatment Of Covid-19-associated Myocarditismentioning
confidence: 99%